The Imperilled Right to Life, Femicide Crisis in South Africa: Critical Considerations for Legislators - Sithomola, T. (International Journal of Criminology and Sociology, 2022)
Femicide is one of the most atrocious acts that are principal causes of premature deaths of women and girls who experience gender-based violence in South Africa. These violent acts that are mainly perpetrated by their male counterparts include inter alia, physical, emotional, psychological and economic violence. Constitutionally, everyone has the right to life, however; the mass killings of women in the hands of males, categorically implies clear inadequacies of the state apparatus to guarantee this valuable human right to women and girls in South Africa. Consulted literature reveals that little has been done in terms of scholarly interrogation of the right to life for women against the heinous femicide crimes committed with no regard for women’s human rights in South Africa. Aim: to explore the deprivation of right to life of those who have fallen victims to the national crisis of femicide. Methodology: for the purpose of this article, the author adopted a qualitative research approach where a variety of non-empirical methods and techniques were employed. The methodological inclination entails a desktop analysis by a means of intensive literature study where information produced has been scholarly scrutinised through a process of intellectual analysis, categorisation, integration, reflection and synthesis where meanings were ascribed to the main themes of this article. Findings: It has been deduced that there are legislative shortcomings that need urgent lawmakers’ attention in order to protect women’s right to life. This implies that femicide law is vital to curb the spate of arbitrary killings of women and girls in South Africa. Additional measures to consider include school-curriculum pre-emptive programmes and community-based advocacy programmes to create a society that honours women’s right to life.